Analysis of Factors Affecting Mango Market Supply in Gomma District, Southwest Ethiopia - Yordanos Teka; Hash Malin; Alemayehu Oljira Wolde (Socio-Economics/Agribusiness Department, 2019)
This study is designed to analyze factors affecting mango market supply and identify the existing market channels in Gomma district, Southwest Ethiopia. Descriptive statistics such as mean, standard deviation & frequencies and multiple linear regressions have been used to analyze the data collected from mango market actors. The study identified seven potential mango market channels in the study area. Producer-Retailer-Consumer marketing channel was identified to be the first and most important mango marketing channel in the study area. It represented 26% of the total mango marketed during the survey period. The result from multiple linear regressions model indicates that from the total of ten independent variables five variables such as quantity of mango tree owned, age, education and access to market information were identified as factors affecting volume of mango market supply. Their magnitude, relationship with quantity of mango market supply and interpretations are given in results and discussion section. Finally, possible policy recommendations have been suggested.